2020
DOI: 10.3390/cells9051151
|View full text |Cite
|
Sign up to set email alerts
|

Functional Roles of Matrix Metalloproteinases and Their Inhibitors in Melanoma

Abstract: The extracellular matrix (ECM) plays an important role in the regulation of the tissue microenvironment and in the maintenance of cellular homeostasis. Several proteins with a proteolytic activity toward several ECM components are involved in the regulation and remodeling of the ECM. Among these, Matrix Metalloproteinases (MMPs) are a class of peptidase able to remodel the ECM by favoring the tumor invasive processes. Of these peptidases, MMP-9 is the most involved in the development of cancer, including that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 155 publications
6
94
0
Order By: Relevance
“…The ability of the walnut septum extract to decrease A172 cell proliferation and migration led to the hypothesis that it could exert a pro-apoptotic action or act against proteases and proteins that favor cell invasion and migration. This has been supported from preliminary animal studies, which found that walnut extracts were effective in reducing the concentration of matrix metalloproteinases at the mRNA and protein level, that are well-known to be involved in tumor invasion ( 78 - 80 ). In the same manner, several studies have demonstrated the pro-apoptotic action of walnut septum polyphenols for example, in human breast cancer cell lines implanted in nude mice, and in mammary gland, prostate, colon, and renal cancers tumors in transgenic mouse models ( 62 , 81 ).…”
Section: Discussionmentioning
confidence: 80%
“…The ability of the walnut septum extract to decrease A172 cell proliferation and migration led to the hypothesis that it could exert a pro-apoptotic action or act against proteases and proteins that favor cell invasion and migration. This has been supported from preliminary animal studies, which found that walnut extracts were effective in reducing the concentration of matrix metalloproteinases at the mRNA and protein level, that are well-known to be involved in tumor invasion ( 78 - 80 ). In the same manner, several studies have demonstrated the pro-apoptotic action of walnut septum polyphenols for example, in human breast cancer cell lines implanted in nude mice, and in mammary gland, prostate, colon, and renal cancers tumors in transgenic mouse models ( 62 , 81 ).…”
Section: Discussionmentioning
confidence: 80%
“…Recently, a growing body of evidence is trying to correlate ICI efficacy to the expression levels of PD-L1 detected in circulating tumor DNA (105,106). Finally, studies have proposed the analysis of matrix metalloproteinase (MMPs), known to be strictly involved in melanoma growth (107,108), as good indicator of response to immunotherapy. Moogk and colleagues (109) showed an inverse association between anti-tumor T-cell response and MMP-23 expression in primary melanoma tumors treated with adjuvant immunotherapy.…”
Section: Immunotherapy Biomarkersmentioning
confidence: 99%
“…Intense research in cancer biology has identified global genomic hypomethylation as one of the leading factors for genomic instability and oncogene activation, whereas a number of tumor suppressor genes are silenced due to hypermethylated CpG islands [ 96 ], while global hypomethylation of lamina-associated domains (LAD) may be another aspect of the deregulated methylome [ 97 ]. In cutaneous melanoma, it was demonstrated that promoter hypomethylation and intragenic hypermethylation of specific genes are associated with tumor aggressiveness due to the alteration of extracellular matrix components and the upregulation of matrix metalloproteinases [ 98 , 99 , 100 ]. This highlights the clinical potential of deregulated methylation status as a hallmark for carcinogenesis, allowing the recognition of various methylation patterns as biomarkers for diagnosis and prognosis [ 101 ] ( Table 1 ).…”
Section: Current Molecular Biomarkers For Nmscmentioning
confidence: 99%